A new insight into male fertility preservation for patients with completely immotile spermatozoa - Chen, Huanhua (Reprod Biol Endocrinol, 2017)
BACKGROUND: Sperm cryopreservation is the most effective method to preserve male fertility but this is normally used for motile spermatozoa. Thus, only motile spermatozoa are used for cryopreservation in most reproductive medicine centers worldwide. The immotile spermatozoa from some problematic patients are usually discarded, resulting in a missed opportunity of sterility cryopreservation for future assisted reproductive treatments. Many studies have shown that successful fertilization can be obtained after selection of viable sperm from the completely immotile spermatozoa before ICSI. Whether the completely immotile spermatozoa are worth of freezing has not been realized The aim of this study is to explore the clinical value of cryopreservation of immotile spermatozoa. METHODS: Completely immotile spermatozoa were collected and frozen, and subsequently viable but immotile frozen-thawed spermatozoa were selected by laser plus for ICSI. Main outcomes included spermatozoa survival index, fertilization rate and good quality embryo rate. RESULTS: After identification by laser, the fresh samples of spermatozoa presented with a mean survival rate of 54.86% and 26.05%, and this was reduced to 44.13% and 18.13% in frozen-thawed spermatozoa samples, which showed a frozen-thawed spermatozoa survival index of 0.80 and 0.70 in the testicular and ejaculate sperm, respectively. There were no statistically differences in fertilization rate (80% vs80.51%, 75.00% vs 81.48%), cleavage rate (95.45% vs 98.95%, 100.00% vs 95.45%) and good quality embryo rate (40.48% vs 52.13%, 33.33%vs38.10%) between the frozen-thawed immotile spermatozoa group and the routine fresh immotile spermatozoa ICSI group in both testicular and ejaculate sperm, respectively. CONCLUSIONS: The results of the study show that completely immotile spermatozoa can be frozen in order to preserve male fertility as long as viable spermatozoa are present. This procedure provides a further possibility for fertility preservation for patients with completely immotile spermatozoa.